Clarification of turbid lake water using novel coagulant from peat soil - Helal Uddin, A.B.M.; Saeed, Mohammad; Mohd Asri, Mohd Nawi (SENTRA Academic Publishers, 2008)
Malaysian peat soil usually categorised as tropical peat soil was chemically modified to work as a coagulant. This coagulant was found very effective for the removal of turbidity from lake and river water in a laboratory scale study. It was found that turbidity could be as low as 5 FTU after treatment with peat coagulant. Besides turbidity there was a reduction of suspended solids and chemical oxygen demand (COD) observed in this study. pH plays an important role for the clarification using peat coagulant. It was found that at acidic pH peat coagulant showed a better clarification compared to basic pH. It was mainly due to the chemical characteristics of the peat coagulant itself. The mechanism for the coagulation was suggested as charge adsorption neutralisation process. The effectiveness of peat coagulant was also compared with the commercial coagulant such as alum. Study revealed that the result obtained for different water quality parameters using alum as a coagulant was comparable with that of peat coagulant.